2007
DOI: 10.1525/jer.2007.2.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Participatory Research and the Ethics Review Process

Abstract: THIS EXPLORATORY STUDY EXAMINES the experiences of community-based participatory researchers' (CBPR) with the IRB. CBPR is oftentimes applied to non-clinical questions where academic researchers collaborate with community partners to address local concerns. Constant Comparative Method guided the analysis of ten CBPR interviews. The interview questions included: How does your conceptualization of research coincide with the regulations' definition? How are community partners involved in the IRB process? What are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 11 publications
1
35
0
Order By: Relevance
“…This oversimplification may further inhibit attempts to develop effective and informed review processes that meet the needs of CBPR while maintaining the core set of principles upon which research ethics is predicated. Our approach is consistent with the moderate position taken by scholars seeking to find commonalities and reconcile these seemingly disparate interests (Ross et al, 2010b;Shore, 2007aShore, , 2007b.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…This oversimplification may further inhibit attempts to develop effective and informed review processes that meet the needs of CBPR while maintaining the core set of principles upon which research ethics is predicated. Our approach is consistent with the moderate position taken by scholars seeking to find commonalities and reconcile these seemingly disparate interests (Ross et al, 2010b;Shore, 2007aShore, , 2007b.…”
supporting
confidence: 78%
“…This may result in situations where REBs/IRBs are approving studies that may be harmful to communities or, conversely, impeding innovative approaches that could have provided much-needed insights into complex issues (Boser, 2007;Bradley, 2007). Indeed, growing critiques have been levied by CBPR practitioners who have found ethics review processes difficult to navigate and unresponsive to their needs (Reid & Brief, 2009;Shore, 2007a). This has been explained, in part, by a lack of appropriate training for reviewers about iterative and participatory approaches to research (Lincoln & Tierney, 2004).…”
mentioning
confidence: 99%
“…CEnR encompasses a range of research practices (Dubois et al 2011;Shore 2007;Shore et al 2010; Sieber ajob pr 19 AJOB Primary Research 2010). On one end is community-based participatory research, in which communities are full partners in shaping research goals, design, implementation, analysis, and dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…another research approach that is frequently identified as encountering difficulties in traditional 'regulatory' research ethics review is participatory and action research (Bhattacharya, 2007;Blake, 2007;Boser, 2007;Burke, 2007;Cahill et al, 2007;Martin, 2007;Owen, 2006;Shore, 2007;Williamson and Prosser, 2002). In addition to the previously addressed challenge of a significantly higher degree of unpredictability regarding the research process, which has an effect on the informed consent process, it also brings up the issue of the definition of the role of both researchers and participants.…”
Section: Ethics Methodology and Social Science And Humanities Researchmentioning
confidence: 99%